Deciphering anti-infectious compounds from Peruvian medicinal Cordoncillos extract library through multiplexed assays and chemical profiling - Vásquez-Ocmín, Pedro G.; Cojean, Sandrine; Roumy, Vincent; Marti, Guillaume; Pomel, Sébastien; Gadea, Alice; Leblanc, Karine; Dennemont, Indira; Ruiz-Vásquez, Liliana; Ricopa Cotrina, Hivelli; Ruiz Mesia, Wilfredo; Bertani, Stéphane; et al. (Frontiers in Pharmacology, 2023)
High prevalence of parasitic or bacterial infectious diseases in some world areas is due to multiple reasons, including a lack of an appropriate health policy, challenging logistics and poverty. The support to research and development of new medicines to fight infectious diseases is one of the sustainable development goals promoted by World Health Organization (WHO). In this sense, the traditional medicinal knowledge substantiated by ethnopharmacology is a valuable starting point for drug discovery. This work aims at the scientific validation of the traditional use of Piper species (“Cordoncillos”) as firsthand anti-infectious medicines. For this purpose, we adapted a computational statistical model to correlate the LCMS chemical profiles of 54 extracts from 19 Piper species to their corresponding anti-infectious assay results based on 37 microbial or parasites strains. We mainly identified two groups of bioactive compounds (called features as they are considered at the analytical level and are not formally isolated). Group 1 is composed of 11 features being highly correlated to an inhibiting activity on 21 bacteria (principally Gram-positive strains), one fungus (C. albicans), and one parasite (Trypanosoma brucei gambiense). The group 2 is composed of 9 features having a clear selectivity on Leishmania (all strains, both axenic and intramacrophagic). Bioactive features in group 1 were identified principally in the extracts of Piper strigosum and P. xanthostachyum. In group 2, bioactive features were distributed in the extracts of 14 Piper species. This multiplexed approach provided a broad picture of the metabolome as well as a map of compounds putatively associated to bioactivity. To our knowledge, the implementation of this type of metabolomics tools aimed at identifying bioactive compounds has not been used so far.